Mini Review Immunological Consequences of Immunization With COVID-19 mRNA Vaccines: Preliminary Results - Lombardi, Andrea; Bozzi, Giorgio; Ungaro, Riccardo; Villa, Simone; Castelli, Valeria; Mangioni, Davide; Muscatello, Antonio; Gori, Andrea; Bandera, Alessandra (Frontiers in Immunology, 2021)
Background BNT162b2 and mRNA-1273 are the two recently approved mRNA-based vaccines against COVID-19 which has shown excellent safety and efficacy. Preliminary data about specific and neutralizing antibodies is available covering the first 100 days after vaccination. Methods We reviewed all the publications regarding the immunologic consequences of BNT162b2 and mRNA-1273 vaccination. A summary of specific antibodies concentration and neutralizing antibodies titres elicited by each vaccine is provided. Results BNT162b2 and mRNA-1273 displayed a profile reassuring safety and efficacy profile, with the latter above 94%. They can elicit specific antibodies titres and neutralizing antibodies concentrations that are far superior from those observed among COVID-19 human convalescent serum, across a wide span of age, for at least 100 days after vaccination. Moreover, the vaccine-induced T cellular response is oriented toward a TH1 response and no evidence of vaccine-enhanced disease have been reported. Discussion BNT162b2 and mRNA-1273 can elicit specific antibodies titres and neutralizing antibodies concentrations above those observed among COVID-19 human convalescent serum in the first 100 days after vaccination. Data about vaccine efficacy in those with previous COVID-19 or immunocompromised is still limited.